Togo : Selected Issues. (IMF Staff Country Reports; Country Report, 2009)
This Selected Issues Paper examines the main channels of transmission of the global financial crisis on Togo's economy. This paper assesses its impact, focusing on 2009 and considering country-specific factors that may aggravate, mitigate, or offset its effects. The decrease in global demand has already brought down the prices of its main exports, phosphate and cotton, which already had problems. The increase in unemployment in Europe and the United States may also affect Togo through lower remittances, which have been a significant source of income.